OPTIMISATION OF MATERIAL, INFORMATION AND MONEY FLOW IN SUPPLY CHAIN MANAGEMENT - Hery Purnomo; Subagyo Subagyo; Faisol Faisol; Dodi Kusuma Hadi Soejoko; Poniran Yudho Leksono (CV. Adiba Aisha Amira, 2025)
This study aims to examine strategies for optimising the flow of materials, information and money in supply chain management (SCM) through the literature review method. Effectively integrated SCM can improve operational efficiency, accelerate response to market demand, and strengthen the company's competitiveness. Material flow optimisation is achieved through accurate demand planning, efficient inventory management, and strategic partnerships with suppliers. Meanwhile, optimised information flow is achieved by the application of digital technology, integration of information systems, and data transparency between supply chain actors. Efficient money flow management involves financial system integration, receivables and payables management, and the utilisation of supply chain finance. The study results show that the synergy of the three flows, supported by technology and collaboration, is essential to create an adaptive, responsive, and sustainable supply chain. This research is expected to be a reference for practitioners and academics in developing more effective supply chain management strategies in the era of global competition.